EGGS IN THE HUMAN DIET - FACTS AND CHALLENGES - Tsvetelina Vitkova; Rositsa Enikova; Milena Karcheva; Plamen Saraliev (Peytchinski Publishing, 2024)
Eggs are a good source of balanced nutritional and biologically active substances - proteins, lipids, some irreplaceable nutritional components such as amino acids, polyunsaturated fatty acids, vitamins, macro- and microelements, etc. It is identified as the cheapest animal source of proteins, lipids, vitamins A, B12, riboflavin, choline, iron, zinc, phosphorus and calcium. At the same time, the dangers to human health that eggs can carry are also taken into account. Material/Methods: The literature used is based on databases PubMed, Embase and as well as data from own studies. Review Results: In the present review, we provide data on the importance of the composition of eggs in human nutrition are presented and the risk of their use is evaluated. Conclusions: The high biological and nutritional value of eggs are grounds for their use in the daily life of healthy people, without additional restrictions of cardiovascular diseases. There is a risk of food poisoning, which can be limited to acceptable levels by following good hygiene practices.